Racing strategy in BMX competiton - Smit, A. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Theories based on time trial studies indicate an advantage of a fast start for short and middle distance cycling events. However, when competing at the same time against other competitors, tactics also plays a role in pacing and winning. The main purpose of this study was to determine which racing strategies elite riders use to distinguish themselves from sub-elite riders. Methods: The measurements were done during a European Championship round of Bicycle Motocross (BMX). The course was 358m long and divided in 6 sections (S1-S6), with the aid of the start, 5 strategic points (T1: after 10m; T2-T5 after each straight) and the finish (TF). With use of multiple video cameras, time and rank on T1-T5 and TF were recorded during the semi-finals of this race in the category Elite Men. From this, split-time, section-speed, normalized split-time, and final-time were determined. Split-ranking and final ranking was also determined. A Student`s t-test was used to determine differences between elite riders (top 5) and sub-elite riders (11-16). Results: Elite riders have a higher normalized split-time (p<0.01) than sub-elite riders on T1 (5.14% vs 4.97%) and T2 (21.77% vs 20.94%). The speed-distance profile shows a declining speed from S2-S6 for sub-elite riders. Elite riders have the same profile, but accelerate on S4. Elite riders ride a significant faster speed (11.09 vs 9.89 m/s) on S4 (p<0.01) than sub-elite riders. Split-times for elite riders was significant faster on T4, T5 and TF. Most rank changes occur on S2-S4 (10, 12 and 9 rank changes respectively), while few rank changes occur on S5-S6 (6 and 4 changes respectively). Discussion: Elite riders in this study distinguish themselves from sub-elite riders in that they use a different racing strategy. Elite riders have a relative faster start and are able to accelerate on S4 where sub-elite riders cannot. This gives elite riders a tactical advantage in the last part of the race, where few rank changes occur. Koning et al. (1999) indicate that an all-out strategy is the best strategy on distances shorter than 1000m, based on a energy-flow model. The speed-distance profile in this study though, resembles more the pattern of a 1500m simulated time trial, as found by Hettinga et al. (2007). One explanation is the influence of tactics on the race strategy (Jones & Whipp, 2002), which is absent in a simulated time trial. Another explanation for the finding is the used gear ratio, which is quite small in BMX, resulting in a quicker acceleration and achieving peak power and peak speed earlier than on a race bike and therefore requiring a more evenly paced strategy as power is generated more quickly resulting in a faster fatique.